Advancing Forensic Flood Analysis Through Hydraulic Physical Models - Sanchez-Quijano, Miguel Angel; Gutierrez-Lopez, Alfonso; Gonzalez Lagunas, Fernanda (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2024)
Urban density significantly increases the multi-hazard risks caused by extreme weather events. In Latin America and the Caribbean (LAC) countries, flood damages in urban areas are considerable and have shown a consistent annual increase. This challenge has prompted innovative educational responses to address the growing need for understanding and managing urban flood risks effectively. As part of postgraduate education efforts, the International Flood Initiative under the Intergovernmental Hydrological Programme of UNESCO for the LAC region (IFI-LAC IHP-UNESCO) aims to enhance understanding of vulnerability and flood risk estimation in urban settings. The initiative encourages the development of advanced hydro-informatic tools, watershed and river modeling techniques, and scale prototype construction to foster practical learning.One of the educational approaches involves analyzing and reconstructing hydraulic infrastructure failures to provide insights into urban flood dynamics. This paper highlights the design and construction of a surface channel and a floodgate system equipped to enable controlled flash openings, capable of triggering crash waves. These facilities allow the recreation of three notable urban flood events, facilitating forensic hydraulic analysis. Detailed similitude analyses are provided, illustrating how sonic water level sensors can be effectively implemented and contributing to the understanding of flood risks and mitigation strategies in densely populated urban environments. Keywords: flood; forensic analysis; hydraulics; open channel; damage; disaster; flash flood; break wall